Residual radiopharmaceutical activity in venous access devices during PET and SPECT imaging: a real-world clinical observational cohort study - Rasmus Solem; Nourhan Al-Amiri; Ida Skarping (EJNMMI Reports, 2026)
Abstract Background In routine practice, radiopharmaceuticals are administered via a newly placed peripheral intravenous catheter (PIVC). However, many patients referred for nuclear medicine imaging already have a semipermanent venous access device in place, such as a central venous catheter, peripherally inserted central catheter, or subcutaneous implantable venous port. Evidence regarding residual radiopharmaceutical activity within preexisting devices—and its potential consequences for SPECT/PET image quality, diagnostic interpretation, and radiation safety—remains limited. This study aimed to quantify device-related residual radiopharmaceutical activity across commonly used access types and to assess any associated clinical impact during image review. Results In this observational cohort study at Skåne University Hospital, Sweden, 167 patient administrations during SPECT or PET imaging between June 2023 and January 2026 were included (40% aged < 18 years). Residual activity was evaluated using ROI/VOI based quantification at the venous access site on reconstructed or planar images. Measurements were performed in an activity meter using PIVCs that had been removed from patients prior to imaging. In an experimental setting, representative venous access devices were flushed under controlled conditions to determine residual activity fraction. Residual activity was expressed both as absolute activity (MBq) and as the percentage of the administered activity. Across 214 measurements including 13 radiopharmaceuticals, residual activity was generally low: only 3.3% of the measurements (7/214) exceeded 5% of the administered activity. The highest absolute residual activity was 31 MBq ([ 99m Tc]pertechnetate, PIVC), and the highest proportional residual activity was 17.3% ([ 99m Tc]Tc-MAA, Midline). On clinical image review, no instance of device related residual activity was associated with impaired interpretation or reduced diagnostic confidence. Conclusions In this real-world cohort, residual radiopharmaceutical activity within preexisting venous access devices was generally low and showed no discernible impact on visual clinical SPECT or PET interpretation. Prospective studies including a broader range of tracers, access devices, and quantitative endpoints are needed to more fully characterize the clinical implications of residual activity.